2016
DOI: 10.1016/j.econedurev.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Who believes in me? The effect of student–teacher demographic match on teacher expectations

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
242
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 432 publications
(290 citation statements)
references
References 33 publications
20
242
2
6
Order By: Relevance
“…Research suggests that a trusting student-teacher relationship is built upon the teacher's consistent warmth and clear expectations, as well the student's high-quality engagement in the classroom (for reviews, see Gregory & Korth, 2016;Sabol & Pianta, 2012;Wang & Degol, 2016). Further support for the interpersonal nature of teacher-student relationships comes from research documenting variability in teachers' relationships with individual students (Gershenson, Holt, & Papageorge, 2016;Gregory & Thompson, 2010). In a seminal study by Gregory and Thompson (2010), adolescents indicated how fair each of their teachers were (e.g., "This teacher treats you more harshly than other students who do better than you in class"), and teachers reported on each adolescent's cooperative behavior in class.…”
Section: Trust In Educational Institutions and Specific Teachersmentioning
confidence: 99%
“…Research suggests that a trusting student-teacher relationship is built upon the teacher's consistent warmth and clear expectations, as well the student's high-quality engagement in the classroom (for reviews, see Gregory & Korth, 2016;Sabol & Pianta, 2012;Wang & Degol, 2016). Further support for the interpersonal nature of teacher-student relationships comes from research documenting variability in teachers' relationships with individual students (Gershenson, Holt, & Papageorge, 2016;Gregory & Thompson, 2010). In a seminal study by Gregory and Thompson (2010), adolescents indicated how fair each of their teachers were (e.g., "This teacher treats you more harshly than other students who do better than you in class"), and teachers reported on each adolescent's cooperative behavior in class.…”
Section: Trust In Educational Institutions and Specific Teachersmentioning
confidence: 99%
“…Indeed, research finds evidence of effects of student–teacher demographic mismatch on teacher behaviors in a variety of contexts. For example, black secondary school teachers have higher expectations for black students’ educational attainment than do white teachers (Gershenson, Holt, & Papageorge, ). Demographically matched teachers also have more frequent positive individual interactions with students (Casteel, ; Meier, Stewart, & England, ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…For instance, teachers may more actively support students of the same race. This may be through higher subjective assessments of ability and educational potential (Gershenson et al, ; Meier & Stewart, ; Ouazad, ) or higher effort on the part of teachers (Keiser et al, ; Meier & Stewart, ). Alternatively, absenteeism may be caused by parental and student discomfort with other‐race teachers through symbolic effects of demographic representation.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Teachers of color devote more time to students of color, judge their learning potential more favorably, and refer them to gifted programs at higher rates (dee, 2004;Grissom, Nicholson-Crotty, & Nicholson-Crotty, 2009;Gershenson, Holt, & Papageorge, 2016). Furthermore, teachers of color who are more informed about minority students' heritage and culture cultivate those students' sense of institutional belonging and their confidence to learn (Murphy & Zirkel, 2015).…”
mentioning
confidence: 99%